Government Investment Spending and Its Role in The Agricultural Sector for The Period (2004-2021) - Adnan Ghanawi * , Maitham; Yahiya Saleh Al- Kubaisi, Lawrence (Journal of Economics and Administrative Sciences, 2024)
The research addresses the reality of government investment spending in Iraq and its potential impact on the agricultural sector. Agriculture is considered one of the most important economic sectors in the country, as it contributes to achieving food security. However, the sector is witnessing several challenges that affect its productivity and development, including the need for more government investment. This study represents an attempt to analyze the impact of government investment spending on the agricultural sector and estimate the extent of its impact on productivity. The study is based on an in-depth review of the available literature and analysis of data related to government investment spending and the performance of the agricultural sector. Through data analysis, the research indicates that there is a negative impact of the lack of government investment on the agricultural sector, and this is reflected in a decline in productivity. Based on these results, the research presents proposals to improve the reality of government investment spending to enhance and develop the agricultural sector, in addition to specific conclusions to improve government investment spending in the agricultural sector, including enhancing financing, providing technical support to farmers, and developing agricultural infrastructure. Paper type: Research Paper